Rescue surgery for neonate with huge rhabdomyoma and left outflow obstruction. (November 2016) - Seki, Hiroshi; Bakhtiary, Farhad; Vollroth, Marcel; Mohr, Friedrich Wilhelm; Kostelka, Martin
We describe a rescue operation in a neonate with a large left ventricular tumor obstructing the left ventricular outflow tract. Surgical resection was performed through an aortotomy and transseptal approach. We excised the main part of the tumor, which was obstructing the outflow tract, leaving a portion that was strongly attached to posterior wall of the left ventricle and mitral valve annulus, which was not feasible to remove. Histological examination showed a rhabdomyoma with benign features. The girl was doing well after 3 months, with no residual tumor growth and no signs of obstruction of the left ventricular outflow tract.